Policy options for healthier retail food environments in city-regions - Mah, Catherine L. (Can J Public Health, 2016)
Public policy is central to health promotion: it determines the distribution of resources in a society and establishes the structural context for the actions of both corporations and consumers. With this in mind, the purpose of this paper is to begin a discussion on promising policy options for a health-promoting retail food environment. Drawing on specific municipal examples, we examine four groups of policy options for healthier retail food environments in city-regions: planning for health; transforming consumer environments; economic and fiscal instruments; and a culture of transparency and participation. We introduce examples of policy options that are receiving increasing attention in the public health and urban planning literature and that function at the municipal level. We also highlight how public health professionals have an important role to play in policy that shapes retail food environments, especially in making explicit the linkages between health and other policy goals. In doing so, this commentary aims to motivate public health practitioners in a variety of community contexts to consider the policy supports they need to advance their exploration, development, testing and evaluation of interventions for healthier retail food environments.